D1.2 Improving outcomes for children with hepatoblastoma, increasing the cure rate, reducing the toxicity of treatment and monitoring and preventing hearing loss: thirty years of international collaboration pioneered from gosh. (4th October 2017) - Brock, P; Pritchard, J; Roebuck, D; Dicks-Mireaux, C; Bellman, S; Rajput, K
Abstract : Background: Cisplatin is a chemotherapy drug used to treat cancer in adults and children. A serious side effect is permanent bilateral hearing loss which in young children severely affects language, learning and development. Project: In 1988, we published our concerns about cisplatin use in children and the detrimental effects on hearing and in 1991 published the Brock grading for ototoxicity in children treated with cisplatin. The Société Internationale d'Oncologie Pédiatrique Epithelial Liver (SIOPEL) collaboration has increased the cure rate for standard-risk hepatoblastoma SR-HB from 30% to >90%. Cardiotoxicity was eliminated by excluding doxorubicin, leaving cisplatin as the key chemotherapy drug. Therefore >60% of children still develop Brock grade ≥1 ototoxicity. In 2005 collaboration began between GOSH and Edward Neuwelt's team in Portland, Oregon who had published extensively on the pre-clinical evidence for Sodium Thiosulfate STS being an otoprotectant against cisplatin induced hearing loss. A clinical research phase III randomised trial of STS otoprotection in SR-HB, SIOPEL6 (International Trial Chair PB, Central Review of Radiology DR and Audiology KR) opened at GOSH in December 2007 extending to 11 countries worldwide (109 evaluable patients). The trial closed to recruitment in December 2014. Results: The 3 year Overall Survival is 98.2% in the STS arm and 92.3% in the control arm. The primary end-point of the trial is the comparison of Brock grade ≥1 hearing level at the age of 3.5 years when the child can comply with pure tone audiometry between the randomised arms. The average age at diagnosis on this trial is 13 months. The last child on the trial will reach 3.5 years of age in September 2017. Discussion: We have shown that administering STS is safe and does not worsen the outcome in terms of survival. (References available on request)